LUCÍA FERNÁNDEZ SECADES, «La oligarquía gijonesa y el gobierno de la villa en el siglo XVIII», prólogo de María Ángeles Faya Díaz, Gijón, Ediciones Trea, 2011, 367 págs. - González Santos, Javier (Cuadernos de Estudios del Siglo XVIII, 2012)
SIN RESUMEN